Pengaruh Terapi Bekam Kering Terhadap Tekanan Darah Pada Pasien Hipertensi Primer: The Effect of Dry Cupping Therapy on Blood Pressure in Primary Hypertension Patients - Candrawati, Sang Ayu Ketut; Sukraandini, Ni Komang (Stikes Wira Medika Bali, 2021)
Background: Hypertension is one of the non-communicable diseases that causes morbidity and mortality in the world where 9.4% of deaths each year are due to complications of hypertension. Hypertension is characterized by an increase in systolic pressure> 140 mmHg and diastole> 90 mmHg. Dry cupping is an alternative therapy used in lowering blood pressure in hypertensive patients. The aim of the study: to determine the effect of dry cupping therapy on blood pressure in primary hypertensive patients. This study is a Quasi-experimental with a One-Group Pretest-Posttest Design approach. The number of samples was 15 patients with primary hypertension who were taken by purposive sampling technique. Measurement of data using digital tension onemed brand. Data analysis using Paired T Test. The results showed that the systolic blood pressure obtained a p value of 0.000 and the diastolic blood pressure obtained a p value of 0.001 which means that there is an effect of systolic and diastolic blood pressure before and after being given dry cupping therapy. Dry cupping therapy can be used as an alternative therapy for patients with primary hypertension.